The unique genomic landscape surrounding the EPSPS gene in glyphosate resistant Amaranthus palmeri: a repetitive path to resistance. (December 2017) - Molin, William; Wright, Alice; Lawton-Rauh, Amy; Saski, Christopher
Abstract Background The expanding number and global distributions of herbicide resistant weedy species threaten food, fuel, fiber and bioproduct sustainability and agroecosystem longevity. Amongst the most competitive weeds, Amaranthus palmeri S. Wats has rapidly evolved resistance to glyphosate primarily through massive amplification and insertion of the 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS ) gene across the genome. IncreasedEPSPS gene copy numbers results in higher titers of the EPSPS enzyme, the target of glyphosate, and confers resistance to glyphosate treatment. To understand the genomic unit and mechanism ofEPSPS gene copy number proliferation, we developed and used a bacterial artificial chromosome (BAC) library from a highly resistant biotype to sequence the local genomic landscape flanking theEPSPS gene. Results By sequencing overlapping BACs, a 297 kb sequence was generated, hereafter referred to as the "EPSPS cassette ." This region included several putative genes, dense clusters of tandem and inverted repeats, putative helitron and autonomous replication sequences, and regulatory elements. Whole genome shotgun sequencing (WGS) of two biotypes exhibiting high and no resistance to glyphosate was performed to compare genomic representation across theEPSPS cassette . Mapping of sequences for both biotypes to the referenceEPSPS cassette revealed significant differences in upstream and downstream sequences relative toEPSPS with regard to both repetitive units and coding content between these biotypes. The differences in sequence may have resulted from a compounded-building mechanism such as repetitive transpositional events. The association of putative helitron sequences with the cassette suggests a possible amplification and distribution mechanism. Flow cytometry revealed that theEPSPS cassette added measurable genomic content. Conclusions The adoption of glyphosate resistant cropping systems in major crops such as corn, soybean, cotton and canola coupled with excessive use of glyphosate herbicide has led to evolved glyphosate resistance in several important weeds. InAmaranthus palmeri, the amplification of theEPSPS cassette, characterized by a complex array of repetitive elements and putative helitron sequences, suggests an adaptive structural genomic mechanism that drives amplification and distribution around the genome. The added genomic content not found in glyphosate sensitive plants may be driving evolution through genome expansion.